Status Gizi dan Pengetahuan Kesehatan Reproduksi terhadap Pemanfaatan Pusat Informasi dan Konseling Remaja (PIK-R) - Tina Yuli Fatmawati; Nel Efni; Filius Chandra (Universitas Baiturrahim, 2022)
Adolescence is a period of transition from childhood to adulthood, at which time there is rapid growth including reproductive function that affects developmental changes, both physical, mental, and social roles. Among adolescents aged 15-19 years, the largest proportion of dating for the first time was at the age of 15-17 years. Around 33.3% of girls and 34.5% of boys aged 15-19 years dating when they are not yet 15 years old. Therefore, it is very important to deliver early reproductive health education to prevent and protect adolescents from risky sexual behavior and other risky behaviors that can affect reproductive health. The purpose of this study was to determine the description of nutritional status, the relationship of knowledge about reproductive health to the use of PIK-R in adolescent girls at STIKes Baiturrahim i. This type of research is quantitative research using a cross sectional approach. The sample was carried out on STIKes Baiturrahim student with a total sample of 92 people taken by purposive sampling. The instrument used in this study was a questionnaire. The data were analyzed by univariate and bivariate analysis. The results of this study are the majority of female students have good nutritional status (57,6%), lack of knowledge about reproductive health (65,2%), 52,2% responden did’t use PIK-R,and there is a relationship between knowledge about reproductive health and the use of PIK-R in female students at STIKes Baiturrahim (p-value = 0,001)